Impact of Corporate Financing Decisions on Firm Value of Listed Hydropower Companies in Nepal - Bhatta, Bhuwaneshwar (Apex Journal of Business and Management, 2025)
This study investigates the impact of corporate financing decisions on the market value of listed hydropower companies in Nepal. Specifically, it examines how financial metrics influence firm value, as measured by market capitalization. The analysis is based on 21 listed hydropower companies in Nepal from 2017 to 2023, comprising 147 observations. The study employs descriptive statistics, correlation analysis, and multiple regression analysis to assess the relationship between the dependent variable (firm value) and five independent variables: earnings per share, net worth per share, return on assets, current ratio, and debt-to-equity ratio. The results reveal that net worth per share has a borderline significant impact on firm value, suggesting a modest role of shareholder equity in market performance. More notably, the debt-to-equity ratio significantly influences firm value, indicating that a balanced capital structure enhances market valuation. Companies with optimal leverage levels appear to be better positioned for market growth. The regression model's F-statistic confirms the collective significance of the financing variables in influencing firm value within the hydropower sector. This study provides actionable insights for stakeholders, suggesting that hydropower companies should focus on achieving a balanced capital structure to optimize debt and equity ratios. Strengthening shareholder equity and carefully managing leverage are critical for enhancing market value and ensuring financial stability.